(3GdUHM GdefHj Yf MjKjI GdeJfHjs - (3jhSa GdHOjYj GdOeTbj GdMdHjs; (3CHhGdWjH CMeO Hf GdMSjf Hf GdMSf Hf YHO GdUeO Hf GdLYaj Gdchaj GdeYQha H` CHj GdWjH GdoeJfHj,J (B354 (3g` s
(3ChdgG (B:s
(3aUeeJ GdYRe Ydi PcQ eNJUQ jMJhj Ydi PcQ CHj GdWjH GdeJfHj hCNHGQg s
(3BNQgG (B:s
(3gPG OYGA jTed cd EfSGf ajLH Cf jfWb Hg cd dSGf hGdMeO ddg Ydi GdJeGe hGdceGd, fLR GdcJGHI s
(3fSNI KGfjIs
(3hecedI aj ChdgG hOGNdgG (B- (3HChQGb bdjdI (B- (3HNW eZjQ s
(3hHgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B115 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B201s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B63 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B14 s
Keywords: (3GdCOHs